Assessing the Farmer’s Sustainable Livelihood Outcome of Rice Sectors Development in Sarawak - Sharon Hou, Wan (Human Resource Management Academic Research Society, 2025)
This study focused on the paddy farmers from the northern and southern parts of Sarawak to identify the relationship between the production, socioeconomic and environmental factors with the sustainable livelihood outcomes of the farmers. The study was conducted in ten locations in Miri and Kuching divisions. This study implemented a qualitative study which adopted the empirical study. To obtain the information regarding the rice production and the livelihood strategy, interviews were conducted with thirty selected respondents. The obtained data were then analysed descriptively. This study demonstrates a need to gather information not only on the production level but on the sustainable practices based on the factors of production. The study revealed that land size, capital, subsidies, and incentives are all factors that have significant effect to the rice production and livelihood of the farmers. Therefore, government intervention in standardizing the Guaranteed Minimum Price (GMP) rate between Sarawak and Peninsular Malaysia is essential to enhance farmer’s income. Paddy cultivation land should be preserved and officially gazetted to prevent its conversion into cash crop plantations as well as ensuring the sustainability of paddy agriculture in Sarawak. Additionally, this study underlines the importance of fair rice pricing and land protection for Sarawak's paddy farmers. It emphasizes the need of taking into account factors other than output levels while developing sustainable lives and addressing climate change. Finally, government intervention and modern agricultural practices will be required to ensure food security, improve farmer quality of life, and ensure the long-term viability of Sarawak's paddy agriculture.